High Glycemic Variability as a Risk Factor for CKD Progression in Type 2 Diabetes with Mild-to-Moderate Kidney Dysfunction - Saigusa, Taro; Watanabe, Kentaro; Takubo, Masahiro; Kosuda, Minami; Yamamotoya, Takeshi; Ishihara, Hisamitsu (Experimental and Clinical Endocrinology & Diabetes, 2025)
This study retrospectively evaluates the risk of chronic kidney disease (CKD) progression in patients with type 2 diabetes and mild-to-moderate reduction in the estimated glomerular filtration rate (eGFR).Sixty-six patients with type 2 diabetes and an eGFR between 45 and 60 mL/min/1.73 m² were included, from April 1, 2014, to March 31, 2015, with an 8-year follow-up ending on March 31, 2023. Baseline clinical parameters, including the body mass index, blood pressure, and biochemical markers, were recorded. The HbA1c and eGFR levels were measured annually. The eGFR slope (mL/min/1.73 m²/year) was used to evaluate the CKD progression.Patients with a negative eGFR slope (n=40) exhibited significantly greater HbA1c fluctuations and a higher coefficient of variation (CV) compared with those with an eGFR decline (P=0.011 for both) and were also markedly older (P=0.049). Logistic regression analysis showed a significant association between each one standard deviation increase in the CV and eGFR decline (odds ratio, 1.99; P=0.041), whereas the HbA1c fluctuation showed a trend toward association.Greater variability in glycemic control is linked to an increased risk for CKD progression in type 2 diabetes with mild-to-moderate kidney dysfunction.
Keywords: chronic kidney disease; glycemic variability; eGFR slope; type 2 diabetes